The Influence of Work Motivational and Work Discipline on Teacher’s Performance in Private Junior High Schoo - Satria, Fajar; Haryadi, Rafly (Lembaga Penerbitan Unversitas Esa Unggul, 2023)
The purpose of this study was to analyze the effects of work motivation and work discipline on the performance of taechers who were working at several junior high schools in Kembangan prefecture, and to see the impacts of teacher’s performance and improvement that affects students, in which the practice of human resource management was reviewed empirically in the field of education and for the surrounding environment. This study uses a cause and effect approach to explain the influence between variables that were identified where the survey is conducted using a research instrument in the form of a questionnaire. The data analysis in this study uses quantitative statistical analysis in nature with the aim for testing the predetermined hypothesis.The SPSS 22 software was used for the data processing and data analysis. The data from 150 teachers were collected from several private junior high schools in Kembangan prefecture. The sampling technique was used as a quota sampling. This study used the normality test, hesteroskodesticity, and multicollinearity. The data analysis was analyzed using the multiple linear regression analysis. The results showed that: There was a positive and significant influence between work motivation and work discipline among teachers on their performance together. Partially there was a positive and significant influence between work motivation on teacher performance. Partially there was a positive and significant influence between teachers’ work discipline on teachers’ performance. The above results proved that the increase in work motivation and work discipline among teachers we have observed, and the teacher’s performance have also increased. Keywords: Work Motivation, Work Discipline, Teacher Performance